2020
DOI: 10.1002/app.50014
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial neural networks to model and interpret electrospun polysaccharide (Hylon VII starch) nanofiber diameter

Abstract: Present work was aimed to develop an artificial neural networks (ANN) model to predict the polysaccharide-based biopolymer (Hylon VII starch) nanofiber diameter and classification of its quality (good, fair, and poor) as a function of polymer concentration, spinning distance, feed rate, and applied voltage during the electrospinning process. The relationship between diameter and its quality with process parameters is complex and nonlinear. The backpropagation algorithm was used to train the ANN model and achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…(C(i)) High accuracies were obtained using ANN, (C(ii)) particularly when compared to multi-linear regression [131]. Study revealed that DoE performed poorly in predicting fibre diameter compared to (D(ii)) ANN [129]. (X -denotes the input feature; Ydenotes the target variable; T -target) [140]; and the fibre diameter for (B) polycaptolactone/gelatin blends [131]; (C) polyurethane [147]; (D) poly(vinyl pyrrolidone) [135];…”
Section: Figure 5 Ann Is a Powerful Modelling Technique In Ehd (A(i))mentioning
confidence: 99%
See 3 more Smart Citations
“…(C(i)) High accuracies were obtained using ANN, (C(ii)) particularly when compared to multi-linear regression [131]. Study revealed that DoE performed poorly in predicting fibre diameter compared to (D(ii)) ANN [129]. (X -denotes the input feature; Ydenotes the target variable; T -target) [140]; and the fibre diameter for (B) polycaptolactone/gelatin blends [131]; (C) polyurethane [147]; (D) poly(vinyl pyrrolidone) [135];…”
Section: Figure 5 Ann Is a Powerful Modelling Technique In Ehd (A(i))mentioning
confidence: 99%
“…ML on the other hand can overcome the aforementioned issues, and hence less effort is spent by researchers in preparing the data. A more pertinent advantage is that ML was reported to outperform a DoE quadratic model in predicting fibre diameter (Figure 5(D)) [129,130].…”
Section: Machine Learning For Electrohydrodynamic Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrospinning gained considerable attention due to its flexibility in fabricating micro/nanoscale polymer fibers for various applications 4,5 . The electrospun fibers are used mainly in infiltration, 5 scaffold fabrication, drug delivery, 6,7 and wound healing 8 . Based on the purpose of the application, the fabrication process can use either a polymer solution or melt phases of polymers.…”
Section: Introductionmentioning
confidence: 99%